“But, what is real life?” On the Aesthetic Existence in De sobremesa by José Asunción Silva - Pino Posada, Juan Pablo (Estudios de Filosofía, 2009)
This piece proposes a thesis according to which the novel De sobremesa by José Asunción Silva accounts for the Novelatory In ux of Art such as it is incarnated in an Aesthethic Existence which is brought inside the philosophical context of “the death of God”, that is, of the Creative Becoming of the World. Therefore, there is a follow up of how the novel problematizes the relationship between the life of the artist and the work of art, and this further enables one to adventure an intepretation of Silva`s suicide in terms of a tragic resolution of that artistic metamorphosis of reality. Four instances of analysis are gone through in the said follow–up. 1) The Space of the Novel as an alternative to the Autobiographical Pact and Space, 2) the marginality of art in burgoise society as a socio-historic manifestation of the novelatory in ux, 3) the formal structure of the novel as the redoubling of the Aesthethic Tendence of Existence, 4) the Metaphysical Absolute as the Artistic Nothingness with Cosmic Potentialities.